1973
DOI: 10.1901/jeab.1973.20-163
|View full text |Cite
|
Sign up to set email alerts
|

THE FORM OF THE AUTO‐SHAPED RESPONSE WITH FOOD OR WATER REINFORCERS1

Abstract: The relation between the form of auto-shaped responses to the lighting of a key and the consummatory responses of pecking grain and (Irinking wvater was examined in pigeons.Responses on the key were analyzed by means of high-speed photography, recordings of the force of contact, and judges' ratings of response-formii based on filni and videotape recordings. The first experiment showed that food-deprived birds presented grain as a reinforcer responded on the key with a grain-pecking movement, while water-depriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
325
1
4

Year Published

1995
1995
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 480 publications
(354 citation statements)
references
References 18 publications
24
325
1
4
Order By: Relevance
“…Latencies to initiate pecking and pecking rates were comparable. Although this might suggest that pecking is a generic response to localized ues signals, as in "sign-tracking" (Hearst & Jenkins, 1974), the higher frequency of very fast pecks observed with water presentations suggests a different pecking topography, a fact that is documented in the literature (Jenkins & Moore, 1973).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Latencies to initiate pecking and pecking rates were comparable. Although this might suggest that pecking is a generic response to localized ues signals, as in "sign-tracking" (Hearst & Jenkins, 1974), the higher frequency of very fast pecks observed with water presentations suggests a different pecking topography, a fact that is documented in the literature (Jenkins & Moore, 1973).…”
Section: Discussionmentioning
confidence: 92%
“…This work suggests that, as with food UCSs, terminal behavior also develops with water UCSs but often its form is different (Boakes, Poli, Lockwood, & Goodall, 1978;Davey & Cleland, 1982;Timberlake, 1983b). With pigeons, Jenkins and Moore (1973) reported that the topography ofautoshaped keypecking differs in response to food and water presentations in a way that resembles the consummatory response: food-induced pecks are more forceful, open-beaked, and of shorter duration, whereas waterinduced pecks are slower, sustained, and closed-beak, and often occur together with swallowing movements. The topography of food-and water-induced terminal responding is also thought to depend on the nature of the signaling stimulus and its interaction with the motivational condition (Timberlake, 1983b).…”
Section: Experiment}mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, rats direct social behaviour at another rat whose presence indicates a future food reward, as rats include social aspects in their feeding behaviour (Timberlake 1975). Thus, pigeons conditioned to peck a key for a food or water reward will also direct 'eating' or 'drinking' pecks to the key, respectively, further showing that the motivation behind each movement affects the motor patterns expressed (Jenkins & Moore 1973). Based on these characteristics, we planned to use FAPs in an attempt to uncover the motivation behind abnormal feather pecking.…”
Section: Fixed Action Patternsmentioning
confidence: 99%
“…In a subsequent testing stage known as the negative automaintenance schedule, or omission phase, subjects continue to approach the CS þ even though these responses are now punished by cancellation of the scheduled reward (Browne, 1976;Jenkins and Moore, 1973;Williams and Williams, 1969). Such behavior suggests that the animal is unable to withhold from making the motor response once it has become associated with food reward, thus reflecting impulsive action or 'motoric impulsivity'.…”
Section: Introductionmentioning
confidence: 99%